Effects of Deep Brain Stimulation on Pausing During Spontaneous Speech in Parkinson’s Disease - Ahn, Ji Sook (J Med Speech Lang Pathol, 2014)
The present study examined pausing patterns in spontaneous speech as a measure of the effect of deep brain stimulation (DBS) of the subthalamic nucleus (STN) on parkinsonian speech. Pauses reflect various aspects of speech and language processes, including motor initiation and linguistic planning. Relatively little attention has been given to pauses in determining the effect of STN-DBS. An examination of pausing may be helpful to understanding how this form of therapy affects these behaviors. Seven individuals with Parkinson’s disease who received surgery for bilateral STN-DBS participated. Spontaneous speech samples were elicited in both the ON and OFF STN-DBS condition. Findings indicated that long pauses (250–3000 ms) in spontaneous speech were significantly shorter and more frequent in the STN-DBS ON condition. Furthermore, the proportion of nonlinguistic boundary pauses was significantly greater with stimulation. The findings support previous studies suggesting that speech motor control and lexical retrieval may be affected by STN-DBS.